تحلیل فعالیة أدوات السیاسة النقدیة في ظل فائض السیولة المصرفیة - بن العاریة, حسین; بلبالي, عبد السلام (Finance and Business Economies Review, 2017)
: This paper deals with the analysis of monetary policy tools in light of the excess liquidity of the banking sector in Algeria for the period 2000-2014. Using the descriptive and analytical approach, the reality of the excess liquidity of the banks was examined and the monetary policy tools used to counter the excess liquidity during the period were presented and evaluated, such as the discount rate, compulsory reserves, liquidity recovery tool and the liquidity deposit on the interest bearing deposit. Through the study, we found that the discount rate instrument has not been effective since the beginning of the liquidity surplus. The liquidity recovery tool, the cash deposit on interest bearing deposits and the mandatory reserves, were effective and active in sterilizing excess liquidity in order.